Problems and Solutions in Chinese Pharmaceutical Industry - Zhu, Xueyi (Transactions on Economics, Business and Management Research, 2024)
The Chinese pharmaceutical industry plays an important role in the Chinese society. With the aging of the population and the improvement of residents' health awareness, it has become a key area to ensure public health and improve the quality of life. In addition, it also contributes to the steady development of Chinese economy, increasing a lot of employment opportunities and promoting scientific and technological innovation. Through the improvement of self-sufficiency in China's pharmaceutical industry, the industry has not reduced its foreign dependence, but increased China's international influence as well. However, it also brings about a series of problems. This study will explain the problems in the pharmaceutical industry from four perspectives of generic drugs, innovation ability, medical insurance payment and supply chain. This paper will review the past and current situation of Chinese pharmaceutical industry through the problems and express the future expectations for the industry. According to these expectations, the relative countermeasures and suggestions will be put forward. This study is of great significance for the healthy development of the Chinese pharmaceutical industry.